Mechanical Chiseling Versus Root Bio-Tillage on Soil Physical Quality and Soybean Yield in a Long-Term No-Till System - da Silva, Gustavo Ferreira; Luperini, Bruno Cesar Ottoboni [UNESP]; de Queiroz Barcelos, Jéssica Pigatto; Putti, Fernando Ferrari [UNESP]; Mooney, Sacha J.; Calonego, Juliano Carlos [UNESP] (MDPI, 2025)
Occasional mechanical intervention can help alleviate compaction symptoms in no-till systems, but its effects compared to well-established crop rotation systems are uncertain. Thus, the aim of this study was to evaluate the effects of mechanical and biological chiseling of the soil (via millet and sunn hemp cover crops) on soil physical properties, root development, and soybean yield in a long-term experiment. The treatments consisted of crops rotations used in the spring harvest: (I) triticale (autumn–winter), millet (spring), and soybean (summer); (II) triticale (autumn–winter), sunn hemp (spring), and soybean (summer); and (III) triticale (autumn–winter), fallow/soil chiseling (spring), and soybean (summer). Mechanical chiseling reduced bulk density and penetration resistance in the upper 0.10 m layer by 6% and 37%, respectively. However, its effects did not extend below this depth. Conversely, millet and sunn hemp maintained higher penetration resistance in surface layers but reduced resistance in deeper layers (0.20–0.40 m) by up to 27% compared to chiseling. These cover crops also improved root growth (up to 71% higher root dry mass), soil microporosity, and total porosity. Notably, sunn hemp enhanced water infiltration (151 mm accumulated) and basic infiltration rate (180 cm h−1), outperforming chiseling by 30% and 85%, respectively. Soybean yield was highest under sunn hemp, with an 18% increase over chiseling. Thus, growing millet and sunn hemp in a long-term production system can improve the soil’s physical properties, ensuring better infiltration, storage, and availability of water in the soil for plants.